2006
DOI: 10.1590/s1677-54492006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Aneurisma verdadeiro bilateral de artéria tibial posterior

Abstract: Neste artigo, faz-se o relato de um caso de aneurisma verdadeiro bilateral da artéria tibial posterior em paciente de 57 anos. Os aneurismas surgiram em épocas diferentes. Os aspectos clínicos, diagnósticos e terapêuticos deste caso são discutidos. Este relato é importante, pois os autores não têm conhecimento de caso semelhante na literatura consultada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The patient had no past history of trauma or infection to justify the aneurysmal formation. She did not have abnormal inflammatory markers either, which decreased the possibility of an inflammatory arteriopathy to be the cause of the aneurysm 1,2,12 . Histopathologic study confirmed the diagnosis of a true medial plantar artery aneurysm.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The patient had no past history of trauma or infection to justify the aneurysmal formation. She did not have abnormal inflammatory markers either, which decreased the possibility of an inflammatory arteriopathy to be the cause of the aneurysm 1,2,12 . Histopathologic study confirmed the diagnosis of a true medial plantar artery aneurysm.…”
Section: Discussionmentioning
confidence: 97%
“…Popliteal aneurysms, especially bilateral ones, are frequently associated with AAA. The femoral artery is the second most common site for true peripheral artery aneurysms, while the distal (infra-popliteal) arteries are rarely affected [4][5][6][7][8][9][10][11][12] . True aneurysm of the plantar artery is very rare.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations